Edge‐hydroxylated Boron Nitride for Oxidative Dehydrogenation of Propane to Propylene - Shi, Lei; Wang, Dongqi; Song, Wei; Shao, Dan; Zhang, Wei‐Ping; Lu, An‐Hui (ChemCatChem, 2017)
Oxidative dehydrogenation of propane to olefins is a promising alternative route to industrialized direct dehydrogenation, but encounters the difficulty in selectivity control for olefins because of the overoxidation reactions that produce a substantial amount of undesired CO2. Here we report edge‐hydroxylated boron nitride, a metal‐free catalyst, that efficiently catalyzed dehydrogenation of propane to propylene with superior selectivity (80.2 %) but with only negligible CO2 formation (0.5 %) at a given propane conversion of 20.6 %. Remarkable stability was evidenced by the operation of a 300 h test with steady conversion and product selectivity. The active BNO. site, generated dynamically through hydrogen ion of B−OH groups by molecular oxygen, triggered propane dehydrogenation by selectively breaking the C−H bond but simultaneously shut off the pathway of propylene overoxidation towards CO2. Olefin generation without a metal: Edge‐hydroxylated boron nitride shows superior selectivity for the oxidative dehydrogenation of propane to propylene with only negligible CO2 formation. The dynamically generated active BNO. site triggers propane dehydrogenation by selectively breaking the C−H bond by concomitantly avoiding propylene oxidation to CO2.